Development of Photography Interactive Learning Media at Politeknik Negeri Media Kreatif - Ni Made Widiastuti; Adryans Adryans (The IJICS (International Journal of Informatics and Computer Science), 2021)
The absence of intelligent sight and sound in learning photography at Politeknik Negeri Media Kreatif (Polimedia) is the foundation of this examination. In the conveyance of photography material encountered a few hindrances. One of the primary obstructions is the absence of clear and simple to-work learning media. Polimedia Photography Study Program is the object of exploration. The particular motivation behind this exploration is to foster supporting instruments for photography topic through intuitive learning media identified with photography, and to help understudies and teachers in learning photography so quality learning expanded adequately and learning destinations. This review utilizes the Multimedia Development Life Cycle (MDLC) technique with six phases, specifically: idea, plan, material assortment, gathering, testing, and conveyance. To create an intuitive Learning Media Photography requires 11 sorts of perspectives, to be specific intro & background pages, fundamental photography, structure, openness, aperture & depth of field, Camera Basics, External Flash Photography Basics, Lens Basics, Practical photography, Types of Photography, Photography Techniques. The subsequent intelligent learning media for Photography endures a couple of moments, which utilized for understudies as Photography learning materials